HUBUNGAN EFIKASI DIRI DAN MINAT BELAJAR TERHADAP HASIL BELAJAR SENI TARI - Anis Widyastuti (Joyful Learning Journal, 2023)
Tujuan Penelitian ini adalah mengetahui adanya hubungan antara efikasi diri dan minat belajar terhadap hasil belajar seni tari. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian korelasi. Subjek penelitian ini berjumlah 100 siswa kelas V SDN Gugus RA Kartini Kabupaten Pati. Teknik pengumpulan data menggunakan angket, wawancara, dan dokumentasi. Sebelum melakukan analisis hipotesis, dilakukan uji prasyarat yaitu uji normalitas, linieritas, multikolinieritas, heteroskesdastisitas, dan autokorelasi. Selanjutnya analisis data dengan statistik desktiptif, analisis korelasi ganda, uji F, dan uji determinasi. Hasil penelitian menunjukkan adanya hubungan yang positif dan signifikan antara efikasi diri dan minat belajar secara bersama-sama terhadap hasil belajar seni tari siswa nilai rhitung = 0,357 yang termasuk dalam kategori rendah serta berkontribusi sebesar 12,8% sedangkan 87,92 dipengaruhi oleh faktor lain yang tidak diteliti. Penelitian ini menunjukkan bahwa hasil belajar seni tari dapat berhasil apabila didukung dengan minat belajar yang disertai efikasi diri siswa yang tinggi. Dance is one of the arts that is studied in the SBdP lesson.The implementation of dance learning in class V at SDN Gugus RA Kartini has not been optimal. There are still many students who get scores below the standard of minimum completeness. Many factors influence student learning outcomes both internally and externally, including self-efficacy and interest in learning. This study aims to determine the relationship between self-efficacy and learning interest towards the learning outcomes of dance lesson. This study uses a quantitative approach to the type of correlation research. The subjects of this study were 100 students of class V at SDN Gugus RA Kartini, Pati Regency. Data collection techniques using questionnaires, interviews, and documentation. Before carrying out the hypothesis analysis, prerequisite tests were carried out, namely normality, linearity, multicollinearity, heteroscedasticity, and autocorrelation tests. Furthermore, data analysis with descriptive statistics, multiple correlation analysis, F test, and determination test. The results showed that there was a positive and significant relationship between self-efficacy and interest in learning together on students' dance learning outcomes rcount = 0.357 which was included in the low category and contributed 12.8% while 87.92 was influenced by other factors that not researched. This research shows that the results of learning the art of dance can be successful if it is supported by an interest in learning accompanied by student self-efficacy.